Mass and rotary inertia sensing from vibrating cantilever nanobeams - Sondipon Adhikari (SPIE Proceedings, 2016)
Nano-mechanical sensing exploiting frequency shift of a cantilever beam to obtain the mass of an object is well established. This paper is aimed at investigating the possibility of sensing mass as well as rotary inertia of an attached object. The rotary inertia of an object gives additional insight into its shape, which is a key motivation of this work. It is shown that by using two modes it is possible to formulate two coupled nonlinear equations, which it turn can be solved to obtain mass and rotary inertia simultaneously from the frequency shifts of first two vibration modes. Analytical results are validated using high fidelity molecular mechanics simulation.